(untitled) (Journal of Tourism and Hospitality Education, 2019)
Tourism thrives in peace. It is a major beneficiary of peace. Nevertheless, it is also be a benefactor to peace if it is planned, developed and managed from the perspectives of building socio-economic foundation, environmental wellness and socio-cultural contacts and communications. Such elements of peace through tourism are applicable to all destinations including provincial, national, local or international. This paper presents the general conceptual foundation on tourism stipulated prosperity and peace and relates this feature with Far West Nepal which is a newly established provincial destination in Nepal. It argues that peace related objectives of tourism can be achieved through planned development, operation and purposeful management of tourism directed to enhancing socio-economic foundations and intercultural relations. The responsibilities for such aspects lie at all actors (hosts and guests) and all levels of government like local, national and provincial. This aspect is truly applicable in Far West a newly growing regional tourist destination where the provincial government is on board with people’s mandate and necessary resources.